Evaluasi Sistem Penyimpanan Berkas Rekam Medis di Klinik X Poncokusumo Kabupaten Malang - Rea Ariyanti; Moh Maulana (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
Storage of medical record files is a key to successful management of a service. Storage is very important to see the patient's medical history and repeat visits, therefore the method of storing medical record files must be properly managed. Therefore, it is necessary to evaluate the storage system so that recommendations for improvements can be found regarding the storage of medical record files. This study aims to evaluate the medical record storage system at the X Poncokusumo Clinic, Malang. This study used a qualitative research design which was carried out at the X Poncokusumo Clinic, Malang with a total sample of 4 people which was carried out from March to July 2023. Data collection used interview and observation techniques. Presentation of data is done in a narrative form. The results of the study show that in the aspect of the objective (context) the storage system has not been achieved due to inadequate infrastructure (input), causing the activity (process) of storing medical record files to be not optimal. As for the results (product) of activities in the filling unit or storage system, it shows that there was a missfile incident and there was physical damage to the patient's medical record file.